Preliminary Hearing Judge - Çukaj (Papa), Lirime; Msc. Denisa Laçi (European Journal of Multidisciplinary Studies, 2020)
A new figure in the judicial system was foreseen in the legal amendments undertaken in the Code of Criminal Procedure, by law no. 35/2017, in the framework of the Justice Reform. The Code of Criminal Procedure has been changed in various aspects, including in here the changes that are related with the subjects of the criminal proceedings. I have previously set out what are the problems that emerged in the criminal process in general, and in the Preliminary phase of Investigation in particular, to understand the effects of this figure and the reason for it to enter into the judicial system. This preliminary investigation control based in ower law now is made by the Preliminary Hearing Judge (PHJ) and the Preliminary Investigation Judge (PIJ). The main task of this article, is to determine the impact that the PHJ has had on the progress of a fair and complete criminal process, since it has been sanctioned by law and has begun its functions. On the other hand what are the issues that this subject presents regarding the functions that the law attributes and their implementation in practice? The main focus of this paper is precisely those legal provisions that have provided for the manner in which this procedural subject operates, to further understand its impact on the criminal process in general and on the preliminary investigation phase in particular. An important aspect is making an overview of the Italian law from where we are based to foresee this judicial figure. After a comparison between these legal provisions we came in conclusion of the problematics that PHJ presents. We outline, at the end of the study, our conclusions arising from the examination of the preliminary session and PHJ, as well as some recommendations that I consider necessary for the process of criminal proceedings, in the light of the changes that have taken place.
Keywords: Preliminary Hearing Judge, Preliminary Hearing, Preliminary Investigation, Decentralized Prosecution, Case Referral to court